ISTO: a Language for Temporal Organisational Information Systems - Nogueira, Vitor (2012)
In this paper we propose to extend the logical framework ISCO (Information System COnstruction language) with an expressive means of representing and implicitly using temporal information. Moreover, we also provide a compilation scheme that targets a logic language with modularity and temporal reasoning.